2020
DOI: 10.1016/j.exphem.2020.09.185
|View full text |Cite
|
Sign up to set email alerts
|

The erythroblastic island niche: modeling in health, stress, and disease

Abstract: Erythropoiesis is one of the most demanding processes in the body, with more than 2 million red blood cells produced every second. Multiple hereditary and acquired red blood cell disorders arise from this complex system, with existing treatments effective in managing some of these conditions but few offering a long-term cure. Finding new treatments relies on the full understanding of the cellular and molecular interactions associated with the production and maturation of red blood cells, which take place withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 119 publications
2
36
0
Order By: Relevance
“…These islands are present at various stages of differentiation in the fetal liver and the adult bone marrow and have a key role in erythroid cell proliferation and differentiation. Erythroblastic islands are increased in patients during periods of stress erythropoiesis 1–3 . We agree that the increase of such Erythroblastic Islands in this patient, probably, was due to erythropoietic enlarged post chemotherapy.…”
Section: Imagesupporting
confidence: 59%
See 1 more Smart Citation
“…These islands are present at various stages of differentiation in the fetal liver and the adult bone marrow and have a key role in erythroid cell proliferation and differentiation. Erythroblastic islands are increased in patients during periods of stress erythropoiesis 1–3 . We agree that the increase of such Erythroblastic Islands in this patient, probably, was due to erythropoietic enlarged post chemotherapy.…”
Section: Imagesupporting
confidence: 59%
“…EBIs are situated predominantly in the bone marrow during steady‐state erythropoiesis. EBI consists of one central macrophage (nurse cell) that extends cytoplasmic protrusions to a ring of surrounding erythroblasts 1,2 . It has been proposed that early in erythroid maturation the macrophages provide required recycled iron from ferritin stocks to the erythroid cells, which is needed for hemoglobin production 3 .…”
Section: Imagementioning
confidence: 99%
“…In addition, a role for EKLF in proper programming of macrophage for island function is suggested by gain-of-function studies in macrophage derived from human iPS cells ( Lopez-Yrigoyen et al, 2019 ). There remains a need to increase the expansion capability of erythroid cells in culture for their clinical use ( Migliaccio et al, 2012 ; Heshusius et al, 2019 ; Olivier et al, 2019 ; Deleschaux et al, 2020 ; Pellegrin et al, 2021 ), and identification of the relevant macrophage subtype can inform approaches to overcome heterogeneity and utilize the optimal cells to aid efficient in vitro erythropoiesis ( Rhodes et al, 2008 ; Hom et al, 2015 ; May and Forrester, 2020 ). Indeed, human island macrophage function can be recapitulated in culture by inclusion of lipids and by glucocorticoid receptor activation ( Falchi et al, 2015 ; Heideveld et al, 2018 ).…”
Section: Summary and Outstanding Questionsmentioning
confidence: 99%
“…However, EBI alterations or defects during steady-state erythropoiesis may not necessarily be manifest as severe phenotypes because adequate coping mechanisms to recover and repair EBIs are only required during stress. This is supported by the fact that EBI macrophages are critical for recovery from stress erythropoiesis in the splenic red pulp ( Sadahira et al, 2000 ; Chow et al, 2013 ; Ramos et al, 2013 ; Jacobsen et al, 2015 ; Liao et al, 2018 ; May and Forrester, 2020 ). Recovery is effectively aided by de novo differentiation of monocytes into macrophages ( Ulyanova et al, 2016 ; Liao et al, 2018 ) and via epo-induced signaling in island macrophage that yields prostaglandin mediators of stress erythroid progenitors ( Chen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 98%
“…This suggested the existence of discrete niches for multipotent and lineage-committed progenitors. The existence of a distinct niche for erythropoiesis comes from classical electron microscopy studies that showed that rare macrophages, adjacent to sinusoids, provide a niche for islands of erythroblast maturation ( 30 ), and these have been the focus of many studies in the field ( 31 ). More recently, Comazzetto et al., demonstrated imaging of unipotent erythroid progenitors and showed that they selectively localize next to perivascular stromal cells that maintain them via SCF production ( 32 ).…”
Section: The Anatomy Of Hematopoiesis Is Spatially Organized By Local Microenvironmentsmentioning
confidence: 99%